2015
DOI: 10.1242/jeb.108613
|View full text |Cite
|
Sign up to set email alerts
|

Vision in avian emberizid foragers: maximizing both binocular vision and fronto-lateral visual acuity

Abstract: Avian species vary in their visual system configuration, but previous studies have often compared single visual traits between two to three distantly related species. However, birds use different visual dimensions that cannot be maximized simultaneously to meet different perceptual demands, potentially leading to trade-offs between visual traits. We studied the degree of inter-specific variation in multiple visual traits related to foraging and anti-predator behaviors in nine species of closely related emberiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 75 publications
4
40
0
Order By: Relevance
“…This finding has important implications for the study of avian visual fields (e.g. Martin, 2014;Moore et al, 2015). From a functional perspective, our results mean that when birds diverge their eyes to reduce the size of their blind areas in order to increase visual coverage, the visual fields may not be as wide as previously reported in the literature.…”
Section: −1supporting
confidence: 55%
See 1 more Smart Citation
“…This finding has important implications for the study of avian visual fields (e.g. Martin, 2014;Moore et al, 2015). From a functional perspective, our results mean that when birds diverge their eyes to reduce the size of their blind areas in order to increase visual coverage, the visual fields may not be as wide as previously reported in the literature.…”
Section: −1supporting
confidence: 55%
“…Eye saccades are used not only to relocate gaze but also to modify the configuration of the visual field. For example, birds can converge their eyes to increase the degree of binocular overlap in front of the head (Martin, 1986), which could have consequences for foraging behavior (Moore et al, 2015). Divergent eye saccades reduce the size of the blind area behind the head, increasing visual coverage around the head (Martin, 1986) and hence the chances of detecting threats (Fernández-Juricic et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The position of these specializations in the retina reveals which part or parts of the visual field are sampled with increased spatial resolving power (SRP) and are thus of particular importance for survival tasks such as location of food and mates, predator surveillance, and obstacle avoidance. In addition to our aforementioned studies, recently a large number of retinal topography studies have revealed important information about retinal organization and evolution in a wide range of birds including waterfowl [Fernández-Juricic et al, 2011a;Lisney et al, 2013a], pen-guins [Coimbra et al, 2012], parrots [Coimbra et al, 2014a], and a variety of passerines [Coimbra et al, 2006[Coimbra et al, , 2009Fernández-Juricic et al, 2011a;Moore et al, 2013Moore et al, , 2015Coimbra et al, 2014b]. Here, as well as providing detailed descriptions of eye morphology and retinal topography in a range of hummingbird species, we tested the following two predictions.…”
Section: Introductionmentioning
confidence: 94%
“…Moroney and Pettigrew, 1987;Fernández-Juricic et al, 2011b;Lisney et al, 2013b;Moore et al, 2013Moore et al, , 2015Krabichler et al, 2015]. Recently, however, Coimbra et al [2014aCoimbra et al [ , b, 2015 pointed out that this approach is problematic.…”
Section: Spatial Resolving Powermentioning
confidence: 99%
See 1 more Smart Citation